Analysis of Social Media Use of Entrepreneurship Economic Education Interest - Putri, Rahmah Dianti; Rizal, Yon; Nurdin, Nurdin (Economic Education and Entrepreneurship Journal, 2023)
This study aims to find out how useful the presence of social media is on student interest in entrepreneurship. This research is a type of quantitative research. The method used is descriptive verification method with an ex post facto approach. Sampling was carried out using the cluster sampling method which used a saturated sample with a total sample of 68 students of Economics Education at the University of Lampung. The results of the findings of this study are expected to contribute to economic science related to the usefulness of social media for students, especially in the field of entrepreneurship.Keywords: Entrepreneurship, social media, studentsDOI: http://dx.doi.org/10.23960/E3J/v6i1.15-21